Antimicrobials, Antibiotic Resistance, Antibiofilm Strategies and Activity Methods 2019
DOI: 10.5772/intechopen.79617
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Control Strategies of Biofilms in the Cultural Heritage

Abstract: Biodeterioration is defined as the undesirable change in the properties of materials caused by the activity of biological agents. This process is complex and involves alterations in the physicochemical and mechanical properties by the action of organisms and depends on the microorganisms involved, type of substrate, and environmental conditions. The biodeterioration of cultural heritage is the physical or chemical damage caused by microorganisms on objects, monuments, or buildings that belong to the cultural h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Moreover, among the isolated bacteria, K. rhizophila IP5, B. licheniformis IP7, and S. maltophilia IP9 were able to form biofilm. This bacterial aggregation is the main cause of biodeterioration, since microorganisms can resist adverse abiotic conditions and many biocides and are also able to deteriorate manufactures (Stewart, 2002;Dakal and Cameotra, 2012;Rivera et al, 2018). This was confirmed by the antibiotic susceptibility test that revealed several resistances for the different strains; indeed, it has been reported that some resistance mechanisms are common to both biocides and antibiotics (Scientific Committee on Emerging and Newly Identified Health Risks [SCENIHR], 2009).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, among the isolated bacteria, K. rhizophila IP5, B. licheniformis IP7, and S. maltophilia IP9 were able to form biofilm. This bacterial aggregation is the main cause of biodeterioration, since microorganisms can resist adverse abiotic conditions and many biocides and are also able to deteriorate manufactures (Stewart, 2002;Dakal and Cameotra, 2012;Rivera et al, 2018). This was confirmed by the antibiotic susceptibility test that revealed several resistances for the different strains; indeed, it has been reported that some resistance mechanisms are common to both biocides and antibiotics (Scientific Committee on Emerging and Newly Identified Health Risks [SCENIHR], 2009).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, it is known that the biodeterioration process can be due to the production of inorganic acids like nitrous and nitric acid and salts like nitrite and nitrate by nitrifying bacteria (Mansch and Bock, 1998). Therefore, the results of FTIR analysis, which highlighted the presence of nitrate residues and gypsum on salt efflorescences, strongly correlate with metabolism of Bacillus, Kocuria, and Paenibacillus species isolated from the hypogeum wall (Laiz et al, 2000;Castrillón Rivera et al, 2019) (Figure 4). In agreement, at high humidity, soluble calcium carbonate is transformed into calcium sulfate, namely gypsum, causing visible salt efflorescence (Atlas et al, 1988).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The biodegradation of cultural heritage is mainly caused by the ability of microorganisms to form biofilms (Rivera et al, 2018). Indeed, bacteria can aggregate and adhere to a surface, forming a group of cells producing an extracellular matrix composed of DNA, proteins and polysaccharides.…”
Section: Evaluation Of Biofilm Formationmentioning
confidence: 99%